Orofacial sarcoidosis: report of three cases - Koutrakis Nicholas E.; Sahu Alisha; Vasilyeva Daria; Peters Scott M. (EDP Sciences, 2022)
Introduction: Sarcoidosis is a systemic non-caseating granulomatous disorder of unknown etiology that may affect multiple organ systems. Head and neck involvement can present in unusual and often nonspecific ways. Observations: We report three cases of sarcoidosis with orofacial manifestations: one African American patient with an existing diagnosis who presented with perioral cutaneous involvement by sarcoidosis, and two Caucasian patients with cases where the initial oral presentation - diffusely affected gingiva in one and intraosseous jaw involvement with resultant dental implant failure in the other - led to workup and establishment of the diagnosis of sarcoidosis. The patients were referred to rheumatology and dermatology for appropriate treatment. Conclusion: Although oral lesions of sarcoidosis are not common, they may be the first clinical manifestation of sarcoidosis. The practitioner should be aware of the possible manifestations and be able to formulate an informed clinical differential diagnosis.